2013
DOI: 10.1371/journal.pone.0075925
|View full text |Cite
|
Sign up to set email alerts
|

The G32E Functional Variant Reduces Activity of PPARD by Nuclear Export and Post-Translational Modification in Pigs

Abstract: Peroxisome proliferator-activated receptor beta/delta (PPARD) is a crucial and multifaceted determinant of diverse biological functions including lipid metabolism, embryonic development, inflammatory response, wound healing and cancer. Recently, we proposed a novel function of porcine PPARD (sPPARD) in external ear development. A missense mutation (G32E) in an evolutionary conservative domain of sPPARD remarkably increases external ear size in pigs. Here, we investigated the underlying molecular mechanism of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 55 publications
3
16
0
Order By: Relevance
“…Taken together, PPARD has an inhibitive effect on chondrogenesis in pig external ears. We have shown that the G32E causative mutation reduces activity of PPARD 9. Therefore, it is conceivable to observe that Erhualian carrying the mutant allele at the G32E site had a faster growth rate of auricular cartilage than Duroc carrying the wild-type allele at this site.…”
Section: Discussionmentioning
confidence: 93%
“…Taken together, PPARD has an inhibitive effect on chondrogenesis in pig external ears. We have shown that the G32E causative mutation reduces activity of PPARD 9. Therefore, it is conceivable to observe that Erhualian carrying the mutant allele at the G32E site had a faster growth rate of auricular cartilage than Duroc carrying the wild-type allele at this site.…”
Section: Discussionmentioning
confidence: 93%
“…Increasingly, it is becoming apparent that developmental signals can be fine-tuned by modulating protein stability, localization, and activity through post-translational modifications [10][11][12]. Palmitoylation is a key post-translational modification that is mediated by a family of Asp-His-HisCys (DHHC)-containing palmitoyl acyltransferases (PATs) [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…; Duan et al . ). Furthermore, genome fragments containing Wnt inhibitory factor 1 ( WIF1 ) and high mobility group AT‐hook 2 ( HMGA2 ) also appear to control ear size in both pigs and dogs (Jones et al .…”
Section: Mutations Identified In Wif1 and Hmga2 Genesmentioning
confidence: 97%